The Use of American and British Lexis in Brunei English - Mohamad Nur Raihan (J-Lalite: Journal of English Studies, 2021)
In pronunciation, influenced by American English, a shift in Brunei English can be observed in the increasing use of [r] in tokens such as car and heard particularly among younger speakers whose pronunciation may be influenced by American English. In contrast, older speakers tend to omit the [r] sound in these tokens as their pronunciation may be more influenced by British English. However, it is unclear whether American English has influenced the vocabulary of Brunei English speakers as the education system in Brunei favours British English due to its historical ties with Britain. This paper analyses the use of American and British lexical items between three age groups: 20 in-service teachers aged between 29 to 35 years old, 20 university undergraduates aged between 19 to 25 years old, and 20 secondary school students who are within the 11 to 15 age range. Each age group has 10 female and 10 male participants and they were asked to name seven objects shown to them on Power point slides. Their responses were recorded and compared between the age groups and between female and male data. The analysis is supplemented with recorded data from interviews with all 60 participants to determine instances of American and British lexical items in casual speech. It was found that there is a higher occurrence of American than British lexical items in all three groups and the interview data supports the findings in the main data. Thus, providing further evidence for the Americanisation of Brunei English and that Brunei English is undergoing change.